2014
DOI: 10.3389/fnbeh.2014.00231
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in Extinction of Contextual and Cued Fear Following Post-Training Whole-Body Irradiation

Abstract: Because of the use of radiation in cancer therapy, the risk of nuclear contamination from power plants, military conflicts, and terrorism, there is a compelling scientific and public health interest in the effects of environmental radiation exposure on brain function, in particular hippocampal function and learning and memory. Previous studies have emphasized changes in learning and memory following radiation exposure. These approaches have ignored the question of how radiation exposure might impact recently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…The next day, or 24 hours after training, the mice were tested for recall of conditioned fear during a six min trial. All freezing data were analyzed using Med Associates software (Georgia and St. Albans, Vermont), as previously described [44]. The software analyzes freezing based on a proprietary algorithm scoring with freezing defined as no movement except respiration.…”
Section: Methodsmentioning
confidence: 99%
“…The next day, or 24 hours after training, the mice were tested for recall of conditioned fear during a six min trial. All freezing data were analyzed using Med Associates software (Georgia and St. Albans, Vermont), as previously described [44]. The software analyzes freezing based on a proprietary algorithm scoring with freezing defined as no movement except respiration.…”
Section: Methodsmentioning
confidence: 99%
“…Neurogenic areas are particularly susceptible to ionizing radiation, and this is especially true for the hippocampus [10], a structure of the brain involved in the formation of explicit memories [11]. Although most studies have found reduced cognitive performance after irradiation, there are also conflicting reports, including one where 4-Gy whole-body X-ray irradiation of young mice resulted in an impaired extinction of memories acquired 2 weeks earlier [12] and another one where 0.25-Gy whole-body 28 Si irradiation enhanced long-term potentiation (LTP) and contextual fear conditioning [13]. The first of these studies is compatible with the recent study by Akers et al [14], demonstrating that hippocampal neurogenesis positively regulates forgetting.…”
Section: Introductionmentioning
confidence: 99%
“…Half of the mice (randomly sorted into two groups until any differences in baseline measurements were non-significant) were placed in a new mouse cage fitting in the irradiator and received whole body irradiation at a dose of 4 Gy (dose rate: 1.25 Gy/min). This dose was selected as that was the dose we used previously to assess post-training irradiation effects on cognitive performance in one-month-old mice [10]. This dose could be relevant in the context of radiation therapy in cancer patients, nuclear contamination from power plants, military conflicts, and bioterrorism.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it would be important to assess whether memory alterations due to radiation exposure could be retrograde. Previously, we showed enhanced contextual and cued fear memory prior to and during extinction following post-training irradiation of one-month-old male mice [10]. Due to the established age-sensitivity of radiation effects in mice with increased sensitivity in younger mice, the prior observed enhanced contextual and cued fear memory prior to and during extinction following post-training irradiation following post-training irradiation of one-month-old male mice could be age-dependent.…”
Section: Introductionmentioning
confidence: 93%